Changes in resting‐state brain networks in writer's cramp - Bahram Mohammadi; Katja Kollewe; Amir Samii; Christian F. Beckmann; Reinhard Dengler; Thomas F. Münte (2011)
Abstract Objectives: Writer's cramp (WC) is characterized by excessive cocontractions of agonist and antagonist hand and forearm muscles during writing. Changes in functional magnetic resonance imaging activation patterns in such conditions can be ambiguous as they might either reflect some aspect of the primary pathophysiological mechanism or, alternatively, may be the result of adaptive actions during task execution. To circumvent this problem, we examined WC patients during rest, i.e., without a task, using independent component analysis (ICA) applied to the blood oxygen level‐dependent time series. Methods: Functionally connected brain networks during rest were defined by ICA to assess differences between WC patients ( n = 16) and healthy controls ( n = 16). Analysis was carried out using FMRIB's Software Library. Results: Two functional networks showed between‐group differences, the sensorimotor network and the default‐mode network. In WC patients, the connectivity was reduced in the left postcentral area and increased in basal ganglia in contrast to healthy controls. These changes were not reversed after treatment with botulinum toxin. Conclusions: In line with other studies, the results show a dysfunction in cortico‐subcortical circuits in WC involving somatosensory cortex, areas interfacing the sensory and motor systems, and putamen contralateral to symptomatic hand. Hum Brain Mapp, 2012. © 2011 Wiley Periodicals, Inc.